Efectividad del secado peritoneal versus lavado peritoneal en pacientes intervenidos por peritonitis secundaria a apendicitis aguda perforada - Grados Aranda, Geordi Maikel Jianpierre (2021)
To compare the effectiveness of peritoneal drying versus peritoneal lavage in patients operated on for peritonitis secondary to acute perforated appendicitis. Materials and methods. Analytical observational study - “Retrospective Cohort” in the general surgery service of the Trujillo Regional Teaching Hospital. 141 medical records were included, distributed into two groups: Group 1, Peritoneal Wash (94) and Group 2, Peritoneal Dry (47). The Chi-square test and RR with a 95% CI were used for the analysis. The effectiveness will be evaluated through the development of postoperative complications in each type of peritoneal cleaning. Results. 20 CHs were recorded in the Peritoneal Wash Group (21.27%), which presented some postoperative complications, and 9 in the Peritoneal Dry Group (19.14%). No association was found between the type of lavage and the development of postoperative complications (RR = 0.087, p = 0.768, 95% CI = 0.549-2.248). The most frequent complication was the Operative Site Infection reported in 20 of the Medical Records, 17 of which were of the Superficial type. Conclusions. Peritoneal drying is just as effective compared to peritoneal lavage in avoiding the development of postoperative complications in patients operated on for peritonitis secondary to perforated acute appendicitis.